Estrés laboral y rendimiento académico de un estudiante de tercero de bachillerato sección nocturna de la Unidad Educativa Jaime Roldós Aguilera - Llumitaxi Sisa, Jessica Maribel (2022)
Work stress is linked to the demands demanded by the environment in which an individual who is working in a certain field develops. For working students, this type of stress can have a significant impact on their academic performance. In the present case study, the situation of work stress and academic performance in a student of the Jaime Roldós Aguilera Educational Unit is analyzed, with the objective of determining the incidence of work stress in the school performance of said student. The techniques and instruments used; They were the student grade record, structured interview, direct observation, medical history, the stress vulnerability questionnaire, and the Holmes-Rahe stress scale. This inquiry maintains a mixed approach with a non-experimental design and a correlational inquiry category. Serving this methodology as a starting point to define the therapeutic approach to work on the student. The findings obtained from the psychological evaluation carried out with the adolescent, denoted high levels of stress in the student, together with signs and symptoms of anxiety, and likewise school grades that framed him within a status of low response to educational demands. These results, in turn, allowed us to determine a fundamental incidence of work stress in the current academic development of the student, which is also associated with the precarious situation that the student experiences at home due to the health of one of his parents.